2014
DOI: 10.1371/journal.pone.0087250
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage, Exome Sequencing and Functional Analyses Identify ABCB6 as the Pathogenic Gene of Dyschromatosis Universalis Hereditaria

Abstract: BackgroundAs a genetic disorder of abnormal pigmentation, the molecular basis of dyschromatosis universalis hereditaria (DUH) had remained unclear until recently when ABCB6 was reported as a causative gene of DUH.MethodologyWe performed genome-wide linkage scan using Illumina Human 660W-Quad BeadChip and exome sequencing analyses using Agilent SureSelect Human All Exon Kits in a multiplex Chinese DUH family to identify the pathogenic mutations and verified the candidate mutations using Sanger sequencing. Quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
2
30
0
1
Order By: Relevance
“…Soon afterwards, Liu et al . also provided evidence that ABCB6 is involved in DUH and noticed the coexistence of pigmentation and ocular abnormalities in their patients with DUH . This result supports the opinion that the ABCB6 protein has an important effect on both pigmentation and ocular development …”
Section: Dyschromatosis Universalis Hereditariasupporting
confidence: 70%
See 1 more Smart Citation
“…Soon afterwards, Liu et al . also provided evidence that ABCB6 is involved in DUH and noticed the coexistence of pigmentation and ocular abnormalities in their patients with DUH . This result supports the opinion that the ABCB6 protein has an important effect on both pigmentation and ocular development …”
Section: Dyschromatosis Universalis Hereditariasupporting
confidence: 70%
“…). Most patients with DUH show skin lesions on the trunk or extremities in infancy or early childhood; the lesions usually stop spreading before adolescence . Histologically, there is an increase or decrease of melanin pigmentation in the basal cells of hyperpigmented lesions or hypopigmented macules, respectively, and pigmentary incontinence can occasionally be observed by light microscopy .…”
Section: Dyschromatosis Universalis Hereditariamentioning
confidence: 99%
“…Moreover, the identity of its physiological substrate, although accepted by most researchers to involve porphyrins or porphyrin-like molecules [5,29], is not entirely clear and is difficult to study due to the hydrophobic character of candidate compounds. Nevertheless, it is clear that human ABCB6 participates in and influences many physiological and pharmacological phenomena on cellular and tissue level: mutations in the ABCB6 gene have been implicated in hereditary forms of coloboma [11], dyschromatosis universalis [12] and pseudohyperkalemia [13]. It has also been suggested that ABCB6…”
Section: Discussionmentioning
confidence: 99%
“…ABCB6 has also been implicated in other genetic diseases such as to ocular colobama (a missing piece of tissue in the eye) and dyschromatosis universalis, which is a genetic disorder of abnormal pigmentation (48, 49). Reported variants associated with these disorders are found in Table 2.…”
Section: Clinical Significance Of Abcb6mentioning
confidence: 99%
“… * This table was curated from the following references: (16, 17, 48, 49, 5459) ** Allele Frequencies MAF% were obtained from NHLBI GO Exome Sequencing Project (ESP) Exome VariantVariant Server (http://evs.gs.washington.edu/EVS/) accessed on August 14, 2017. …”
Section: Figurementioning
confidence: 99%